Assessment of Two Commonly used Dermal Regeneration Templates in a Swine Model without Skin Grafting - Eisler, Wiebke; Baur, Jan-Ole; Held, Manuel; Rahmanian-Schwarz, Afshin; Daigeler, Adrien; Denzinger, Markus (Applied Sciences, 2022)
In the medical care of partial and full-thickness wounds, autologous skin grafting is still the gold standard of dermal replacement. In contrast to spontaneous reepithelializing of superficial wounds, deep dermal wounds often lead to disturbing scarring, with cosmetically or functionally unsatisfactory results. However, modern wound dressings offer promising approaches to surface reconstruction. Against the background of our future aim to develop an innovative skin substitute, we investigated the behavior of two established dermal substitutes, a crosslinked and a non-crosslinked collagen biomatrix. The products were applied topically on a total of 18 full-thickness skin defects paravertebrally on the back of female Göttingen Minipigs—six control wounds remained untreated. The evaluation was carried out planimetrically (wound closure time) and histologically (neoepidermal cell number and epidermis thickness). Both treatment groups demonstrated significantly faster reepithelialization than the controls. The histologic examination verified the highest epidermal thickness in the crosslinked biomatrix-treated wounds, whereas the non-crosslinked biomatrix-treated wounds showed a higher cell density. Our data presented a positive influence on epidermal regeneration with the chosen dermis substitutes even without additional skin transplantation and, thus, without additional donor site morbidity. Therefore, it can be stated that the single biomatrix application might be used in a clinical routine with small wounds, which needs to be investigated further in a clinical setting to determine the size and depths of a suitable wound bed. Nevertheless, currently available products cannot solely achieve wound healing that is equal to or superior to autologous tissue. Thus, the overarching aim still is the development of an innovative skin substitute to manage surface reconstruction without additional skin grafting.
CRIS-Team Scopus Importer:2022-04-15
Keywords: animal model; dermal regeneration; Integra; Matriderm; skin substitute; wound healing

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Label-free discrimination of extracellular vesicles from large lipoproteins. - Kashkanova, Anna D.; Blessing, Martin; Reischke, Marie; Baur, Jan-Ole; Baur, Andreas; Sandoghdar, Vahid; Van Deun, Jan (Journal of Extracellular Vesicles, 2023)
Extracellular vesicles (EVs) are increasingly gaining interest as biomarkers and therapeutics. Accurate sizing and quantification of EVs remain problematic, given their nanometre size range and small scattering cross-sections. This is compounded by the fact that common EV isolation methods result in co-isolation of particles with comparable features. Especially in blood plasma, similarly-sized lipoproteins outnumber EVs to a great extent. Recently, interferometric nanoparticle tracking analysis (iNTA) was introduced as a particle analysis method that enables determining the size and refractive index of nanoparticles with high sensitivity and precision. In this work, we apply iNTA to differentiate between EVs and lipoproteins, and compare its performance to conventional nanoparticle tracking analysis (NTA). We show that iNTA can accurately quantify EVs in artificial EV-lipoprotein mixtures and in plasma-derived EV samples of varying complexity. Conventional NTA could not report on EV numbers, as it was not able to distinguish EVs from lipoproteins. iNTA has the potential to become a new standard for label-free EV characterization in suspension.
EVALuna2:538267

The Goettingen minipig as an experimental model in wound-healing studies - Eisler, Wiebke; Held, Manuel; Rahmanian-Schwarz, Afshin; Baur, Jan-Ole; Daigeler, Adrien; Denzinger, Markus (JPRAS Open, 2024)
Background: Deep dermal wounds in extensive burns and chronic wound-healing disorders represent a significant medical problem and require a high level of therapy to reduce the risk of infection and other long-term consequences, such as amputation. A better understanding of the wound-healing processes is essential, and animal models are indispensable to fundamental research. Objective: This study aimed to provide a transparent protocol and prove the effectiveness of an in vivo porcine model using Goettingen minipigs for wound-healing studies. Material and methods: Thirteen female Goettingen minipigs were kept in species-appropriate housing and were treated according to the German law for the protection of animals. The study was performed with permission from the local ethical review committee of animal welfare. The experimental procedure for studying dermal regeneration in 102 full-thickness wounds through clinical observation and histological analysis, focusing on neodermal formation, is described in detail. Results: The Goettingen minipig model proved to be suitable in wound-healing studies. The dermal regeneration was evident and viewable without wound contamination or any rejection reaction. The histological evaluations were also reliable and clearly presented the optimized wound healing of deep dermal wounds using the different therapeutic approaches. Conclusion: Given the great clinical need for alternative or complementary therapies, we considered the Goettingen minipig trial a reliable, ethically justifiable, effective, and reproducible in vivo model for wound-healing studies.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Animal model; Goettingen minipig; Tissue engineering; Wound healing

The Topical Effect of rhGDF-5 Embedded in a Collagen–Gelatin Scaffold for Accelerated Wound Healing - Eisler, Wiebke; Held, Manuel; Rahmanian-Schwarz, Afshin; Schiefer, Jennifer; Rahmanian, Shahab; Daigeler, Adrien; Baur, Jan-Ole (Applied Sciences, 2022)
The application of exogenous growth factors such as the recombinant human growth and differentiation factor 5 (rhGDF-5) represents a major research topic with great potential for the treatment of complex wounds. In a randomized, controlled minipig study, the topical effect of rhGDF-5 on full-thickness skin defects was evaluated. A total of 60 deep dermal wounds were either treated with rhGDF-5 embedded in an innovative collagen scaffold or another commonly used collagen matrix or left untreated. Wound healing was analyzed by planimetric analysis to determine wound closure over time. After 21 days, the areas of the initial wounds were excised, and the newly formed tissue was examined histologically. In comparison to untreated wounds, all examined matrices accelerated dermal wound healing. The largest acceleration of wound healing was seen with the high-dose rhGDF-5-treated wounds, which, compared to the untreated wounds, accelerated wound healing by 2.58 days, improved the neoepidermal thickness by 32.40 µm, and increased the epidermal cell density by 44.88 cells. The innovative collagen scaffold delivered rhGDF-5 adequately, served as a template to guide proliferating and restructuring cells, and accelerated wound healing. Thus, this composite product offers a novel tool for developing effective wound dressings in regenerative medicine.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Collagen scaffold; Composite biomaterial; Growth factor; RhGDF-5; Wound healing